Recent explanatory trials of the mode of action of drug therapies on lipoprotein metabolism - Chan, Dick C; Barrett, P Hugh R; Watts, Gerald F (Current opinion in lipidology, 2016)
Dysregulated lipoprotein metabolism leads to increased plasma concentrations of atherogenic lipoproteins. We highlight the findings from recent studies of the effect of lipid-regulating therapies on apolipoprotein metabolism in humans employing endogenous labelling with stable isotopically labelled isotopomers. Fish oil supplementation and niacin treatment both reduce fasting and postprandial triglyceride levels by decreasing the hepatic secretion of VLDL-apoB-100 (apoB) and apoB-48-containing chylomicron particles in obese and/or type 2 diabetes. Niacin also lowers plasma LDL-apoB and Lp(a) levels by increasing catabolism of LDL-apoB and decreasing secretion of Lp(a), respectively. In subjects with hypercholesterolaemia, inhibition of cholesteryl ester transfer protein raises apoA-I and lowers apoB by decreasing and increasing the catabolism of HDL-apoA-I and LDL-apoB, respectively. Antisense oligonucleotides directed at apoB mRNA lowers plasma LDL-cholesterol and apoB chiefly by increasing the catabolism and decreasing the secretion of LDL-apoB in healthy subjects. That apoB ASO treatment does not lower hepatic secretion in humans is unexpected and merits further investigation. Kinetic studies provide mechanistic insight into the mode of action of lipid lowering therapies and lipoprotein disorders. Understanding the mode of action of new drugs in vivo is important to establish their effective use in clinical practice.